Müllerian papilloma of the rectovaginal septum - Valsangiacomo, Pablo; Ruso, Luis; Ormaechea, Ernesto; Mesa, Marcelo; Boudrandi, Sonia; Harretche, Martín (Cirugía del Uruguay, 2005)
Clínica/ presentation of a fifty-one year old fema/ e patient who carried Müller's papilloma in rectovaginal septum. These tumors are rare and their origin is embryologic; they are the remains of paramesonephrical or ducts of Mül/er fusion from which deve/op the uterus and the upper sector of vagina. They are frequent in girls, exceptional in adults and they appear as genitorrhage or tumoration of the vaginal sac fundus; very rarely do they produce straining or rectal tenesmus. They are benign tumors having p/eomorphic morpho/ogy, with a we/1 defined histologic and immunohistochemical profile and /ow possibility of turning ma/ignant. Their clinical presentation with rectal syndrome elements, the exceptional nature of this type of les ion, its uncertain diagnosis and the surgica/ tactics adopted, confer interest to this communication.